Mermoz© simulator: use of a database to estimate the photovoltaic input on a UAV. Application to a transatlantic voyage - Vincent Boitier; Vincent Mahout; Jean-Marc Moschetta; Nikola Gavrilovic (Drone Systems and Applications)
This paper introduces the Mermoz simulator, developed to predict the photovoltaic energy contribution of solar cells mounted on a low-altitude unmanned aerial vehicle (UAV) over long-distance flights. This MATLAB-based tool implements a modular model of the UAV and its environment from an energy-focused perspective. Leveraging 20 years of data from the NASA Prediction of Worldwide Energy Resource Weather Database, the simulator provides an estimate of the confidence interval for solar and wind energy contributions expressed in Wh, or, to facilitate comparisons, in earned kilometers. Its modular design enables easy testing and comparison of various configurations and flight strategies (e.g., optimal departure times, autonomy gains, or cruise speeds). To facilitate understanding, the structure and operation of the simulator are illustrated using the Mermoz drone as a case study. The Mermoz UAV features a 4 m wingspan and is powered by an electric propulsion system. It combines a fuel cell with a liquid hydrogen tank, enabling fully electric, greenhouse gas-free flight. Simulation results indicate that wing-mounted solar cells can provide up to 5% additional electrical energy during a transatlantic flight.